THE INFLUENCE OF WATCHING PORNOGRAPHY FREQUENTLY THROUGH INTERNET MEDIA ON THE BEHAVIOR OF SEXTING IN ADOLESCENTS IN KABUPATEN TANAH BUMBU: THE INFLUENCE OF WATCHING PORNOGRAPHY FREQUENTLY THROUGH INTERNET MEDIA ON THE BEHAVIOR OF SEXTING IN ADOLESCENTS IN KABUPATEN TANAH BUMBU - Ritna Udiyani; Atmaja, Bayu Purnama; Sadiah, Halimatus (WELL BEING, 2023)
Teenage awareness of reproductive organ maturity encourages to search for sexually related matters due to the development of technology and communication among adolescents by easily accessing pornographic content. The aim of this study was to determine the influence of watching pornography frequently through internet media on the behavior of sexting in adolescents. This study design was a Mixed Method with a quantitative method by using survey analytical with a cross-sectional approach and a qualitative method with a phenomenological approach. Samples in this quantitative study were 283 respondents by using cluster random sampling, the study instrument used a questionnaire while the qualitative study were 6 respondents by using snowball sampling. The results of the quantitative method by using the Spearman rank indicated that the frequency variable watching pornography with the Sexting behavior p value 0.000 (<0.05), which means that H0 was rejected and H1 was accepted. The results of a qualitative study indicated that the first sub-themes of sexting behavior were the types of behavior of sending, receiving forwarding text, photos and videos that were sexual redundant. The second sub-theme of sexing behavior is the various reasons for doing text as a need and language.